Homer's simile, Vyasa's story - Allen, N (Mediterranean Institute, University of Malta, 1996)
Odysseus in the Odyssey and Arjuna in the Sanskrit Mahabharata are comparable heroes, and their respective journeys to Scheria and Heaven both involve comparable ordeals, during which reference is made to joyous relief. The Greek reference comes in a simile, the Sanskrit one comes in the main story. It is argued that the original protonarrative resembled the Sanskrit: Homer's simile is an innovation.